Heat shock protein 70 increases cell proliferation, neuroblast differentiation, and the phosphorylation of CREB in the hippocampus - Hyun Jung Kwon (Laboratory Animal Research, 2019)
Abstract In the present study, we investigated the effects of heat shock protein 70 (HSP70) on novel object recognition, cell proliferation, and neuroblast differentiation in the hippocampus. To facilitate penetration into the blood–brain barrier and neuronal plasma membrane, we created a Tat-HSP70 fusion protein. Eight-week-old mice received intraperitoneal injections of vehicle (10% glycerol), control-HSP70, or Tat-HSP70 protein once a day for 21 days. To elucidate the delivery efficiency of HSP70 into the hippocampus, western blot analysis for polyhistidine was conducted. Polyhistidine protein levels were significantly increased in control-HSP70- and Tat-HSP70-treated groups compared to the control or vehicle-treated group. However, polyhistidine protein levels were significantly higher in the Tat-HSP70-treated group compared to that in the control-HSP70-treated group. In addition, immunohistochemical study for HSP70 showed direct evidences for induction of HSP70 immunoreactivity in the control-HSP70- and Tat-HSP70-treated groups. Administration of Tat-HSP70 increased the novel object recognition memory compared to untreated mice or mice treated with the vehicle. In addition, the administration of Tat-HSP70 significantly increased the populations of proliferating cells and differentiated neuroblasts in the dentate gyrus compared to those in the control or vehicle-treated group based on the Ki67 and doublecortin (DCX) immunostaining. Furthermore, the phosphorylation of cAMP response element-binding protein (pCREB) was significantly enhanced in the dentate gyrus of the Tat-HSP70-treated group compared to that in the control or vehicle-treated group. Western blot study also demonstrated the increases of DCX and pCREB protein levels in the Tat-HSP70-treated group compared to that in the control or vehicle-treated group. In contrast, administration of control-HSP70 moderately increased the novel object recognition memory, cell proliferation, and neuroblast differentiation in the dentate gyrus compared to that in the control or vehicle-treated group. These results suggest that Tat-HSP70 promoted hippocampal functions by increasing the pCREB in the hippocampus.